SOFT SKILLS MODEL BASED SCHOOL CULTURE TO DEVELOPMENT STUDENT CHARACTER FOR ELEMENTARY SCHOOL STUDENTS - Umi Handayani; Sri Utaminingsih; Slamet Utomo (Universitas Muria Kudus, 2020)
This study aims to develop a soft skills model based school culture for character education for elementary school students.This study is a Research and Development study with a modified Sugiyono model. This research was conducted in 3 elementary schools in the target area of III, Jekulo District, Kudus Regency. Data collection techniques using test techniques and non-test techniques. Data analysis in this study was carried out descriptively quantitative and statistical tests using t-test.The results of the research were in the form of a soft skills model design product based on school culture which had components of goal setting, soft skill values, school culture and character education. The soft skills model based on school culture is suitable for use as a learning model in elementary schools. The results of the t test show that t count bigger than t table, so that the soft skills model based on school culture is effectively applied in learning.